2022
DOI: 10.3390/rs15010136
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Impervious Surface Area Mapping and Pattern Evolution of the Yellow River Delta Using Sentinel-1/2 on the GEE

Abstract: The ecological environment of Yellow River Delta High-efficiency Ecological Economic Zone (YRDHEEZ) is adjacent to the Bohai Sea. The unique geographical location makes it highly sensitive to anthropogenic disturbances. As an important land surface biophysical parameter, the impervious surface area (ISA) can characterize the level of urbanization and measure the intensity of human activities, and hence, the timely understanding of ISA dynamic changes is of great significance to protect the ecological safety of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Several other studies evaluated scene-optimized spectral index thresholds with strong accuracy (>90%) on individual subscenes of Sentinel-2 imagery [7,79]. One recent study used fusion of Sentinel-1 SAR and Sentinel-2 time series with manual training data and a random forest achieving an accuracy of 94.8% over the Yellow River Delta [80]. Another used Sentinel-2 imagery with convolutional neural networks and automated training data selection across 12 international cities to map human settlement extent had overall accuracies JSTARS-2023-01104 ranging from 81.8% to 94.8% [81].…”
Section: Discussionmentioning
confidence: 99%
“…Several other studies evaluated scene-optimized spectral index thresholds with strong accuracy (>90%) on individual subscenes of Sentinel-2 imagery [7,79]. One recent study used fusion of Sentinel-1 SAR and Sentinel-2 time series with manual training data and a random forest achieving an accuracy of 94.8% over the Yellow River Delta [80]. Another used Sentinel-2 imagery with convolutional neural networks and automated training data selection across 12 international cities to map human settlement extent had overall accuracies JSTARS-2023-01104 ranging from 81.8% to 94.8% [81].…”
Section: Discussionmentioning
confidence: 99%
“…The remote sensing image datasets were preprocessed via geometric correction and radiation correction. Strip restoration was performed using the focus statistics and fusion function for 2005 data alone, and then all images meeting the temporal and spatial requirements in the study area were stitched according to their median values using the image mosaic function, and finally, the remote sensing image data of the study area were cropped using the cropping function [39]. The workflow diagram is shown in Figure 2 [40], and photographs of some reservoirs in the study area are shown in Figure 3 [41].…”
Section: Methods For Extracting Reservoir Informationmentioning
confidence: 99%
“…One of the current research hotspots is to achieve more comprehensive and accurate monitoring and analysis of river environment by combining remote sensing image analysis technology [8]. Scholars in this field often use multimodal data sources, such as remote sensing image data, geographic information data, and environmental monitoring data, to conduct comprehensive analysis of rivers [9]. They use deep learning techniques such as Convolutional Neural Networks (CNN) and Recurrent Neural Networks (RNN) to process multimodal data and extract and analyze key indicators such as river water quality [10], vegetation, and terrain.…”
Section: Introductionmentioning
confidence: 99%